Implementasi Internet of Things dengan Smart Faucet pada Sistem Irigasi Subak Bali - Putra, Ida Bagus Rahadi; Sanjaya ER, Ngurah Agus (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2025)
This research proposes the implementation of the internet of things with smart faucets in Bali's Subak irrigation system by using algorithms used to implement the internet of things. Sensors including temperature sensors, soil moisture sensors, rainfall sensors, and water level sensors, are installed to monitor real-time environmental and crop conditions. The data collected from these sensors is used in algorithms that are used to optimize water usage according to crop needs and environmental conditions. The results of this study show that there is a reduction in water wastage and an increase in water use efficiency with more accurate control. The optimized irrigation system ensures a water supply that matches the needs of the plants, improves plant growth, and reduces the risk of disease. Users can monitor and control the irrigation system remotely through the website, providing accurate information about the condition of the plants and their water needs. It is an innovative solution to improve crop yields, plant health, and water use efficiency in Bali's Subak irrigation systems.